Study the universal critical congenital heart disease screening in a peripheral area of Uttarakhand, India - Sahota, Ravi; Kaur, Navpreet; Singh, Gurpal; Joshi, Veena; Gahtori, Bharti; Mehrotra, Divya; Upadhyay, Nisha (International Journal of Contemporary Pediatrics, 2020)
Background: Congenital heart disease (CHD) is the most frequently occurring congenital disorder, responsible for 28% of all congenital birth defects. The birth prevalence of CHD is reported to be 8-12/1000 live births. Considering a rate of 9/1000, about 1.35 million babies are born with CHD each year globally. Objective of research work to study the prevalence of CHD among newborn and its types. Methods: This cross-sectional study was carried among 34 cases of CHD/5126 newborn screened at 4 birthing places in Kashipur a small town in Uttrakhand at pediatrics department of Sahota Super-specialty hospital, Kashipur, Uttarakhand. Screening program between 22 August 2014, and March 30, 2019. All newborns, including preterm babies, delivered in these facilities were eligible for inclusion in this study. Results: Present study found the prevalence of CHD was 0.7 per 1000 children (34/5126). Around 26.5% participants have cyanotic CHD and 73.5% have acynotic CHD. Almost 44%, 28%, 20%, 4% and 4% participants of acynotic congenital heart diseases have VSD, ASD, PDA, AVSD and valvular PS respectively and 55.6%, 22.2%, 11.1% and 11.1% participants of cynotic congenital heart diseases have TOF, DORV/VSD, dTGA/VSD and tricuspid atresia respectively. Conclusions: Screening for congenital heart disease should be included as a part of newborn assessment as it is a common congenital problem. Early identification influences outcome. Barriers in implementation of the screening programmes in resource limited setting is a challenging feature. This study can provide observed data that can help in policy making in the health sector.